Chemical Sensors for Water Detection in Organic Solvents and their Applications. Issue 4 (26th January 2021) - Kumar, Pawan; Ghosh, Amrita; Jose, D. Amilan
Abstract: Moisture or trace water detection at a very low level in organic solvents and other chemical reagents has great significance in the chemical and industrial process. At present, reports on chemical sensors for moisture are still in the early development phase and need continuous improvements. Recently, several approaches have been proposed for the easier detection of water content in the organic solvents. In this review article, we have summarized recent reports on chemical sensors used to detect water in organic solvents. The discussion is focused on optical methods, including fluorescent and colorimetric probes exploring solvatochromism, displacement of ligand or metal and water‐induced protonation. Besides, water detection in organic solvents by NMR spectroscopy is also discussed. Probe structure, sensitivity with organic solvents, spectroscopy detection limits, and possible application in various other research areas, including ink‐less writing, sweat pore mapping, food products and engineering materials are described in detail. Abstract : This review describes the overview and recent developments of chemical sensors for water detection in organic solvents. Probes structure, sensitivity, the limit of detection (LOD) and their possible application in various other research areas are described in detail.